International Capital Markets : Recent Develpments and Short-Term Prospects, 1981. (Occasional Papers; Occasional Paper ;, 1981)
This paper provides a review of recent developments and an assessment of short-term prospects for private international capital markets, which constitute one of the main sources of international capital flows.